Adalimumab in Active and Inactive, Non-Infectious Uveitis: Global Results from the VISUAL I and VISUAL II Trials. (2nd January 2019) - Goto, Hiroshi; Zako, Masahiro; Namba, Kenichi; Hashida, Noriyasu; Kaburaki, Toshikatsu; Miyazaki, Masanori; Sonoda, Koh-Hei; Abe, Toshiaki; Mizuki, Nobuhisa; Kamoi, Koju; Brézin, Antoine P.; Dick, Andrew D.; et al.
ABSTRACT: Purpose : Report global adalimumab safety and efficacy outcomes in patients with non-infectious uveitis. Methods : Adults with non-infectious intermediate, posterior, or panuveitis were randomized 1:1 to receive placebo or adalimumab in the VISUAL I (active uveitis) or VISUAL II (inactive uveitis) trials. Integrated global and Japan substudy results are reported. The primary endpoint was time to treatment failure (TF). Results : In the integrated studies, TF risk was significantly reduced (hazard ratio [95% CI]) with adalimumab versus placebo (VISUAL I: HR = 0.56 [0.40–0.76], p < 0.001; VISUAL II: HR = 0.52 [0.37–0.74], p < 0.001). In Japan substudies, no consistent trends were observed between groups (VISUAL I: HR = 1.20 [0.41–3.54]; VISUAL II: HR = 0.45 [0.20–1.03]). Adverse event rates were similar between treatment groups in both studies (854 to 1063 events/100 participant-years). Conclusions : Adalimumab lowered time to TF versus placebo in the integrated population; no consistent trends were observed in Japan substudies. Safety results were consistent between studies.